Synthesis of B4C/YTZP Composite Powder and Studying Effect of its Addition on Mechanical Properties of B4C - Fadhil A. Chyad; Mohammed H. AL-Taie; Hussein AlaaJaber (Engineering and Technology Journal, 2014)
In this research B4C powder have been coated with yttria stabilized tetragonal zirconia polycrystalline (YTZP) (ZrO2 – 6wt% Y2O3) by using sol-gel method in order to obtain on composite powder (B4C core/ YTZP shell, 1/1 wt%). Zirconium oxychloride (ZrOCl2.8H2O) and yttrium nitrate (Y(NO3)3.6H2O) were used as the precursors for synthesis of the YTZP compound. The coated B4C powder was then used as additive powder to B4C. It was mixed with different percentages for making ceramic–ceramic composite samples. The YTZP weight percentages added to the B4C were in the range (0–12.5) wt%. The samples sintered by using spark plasma sintering technique at 1800 and 1900°C for 5 min. Density and mechanical properties (Vickers microhardness, fracturetoughness and fracturestrength) for the sintered samples were measured. The results show that the best YTZP additions to the B4C that have good mechanical properties were ranged 5 – 7.5 wt%.